Legal Consequences of Inheritance Transferred Without the Heirs' Consent (Case Study No.: 107/Pdt.G/2019/Pn. Plk) - Carren Catherina (Eduvest - Journal of Universal Studies, 2024)
This research discusses the legal implications of inheritance transfer without the consent of heirs based on Study Verdict No. 107/Pdt.G/2019/Pn. Plk, the responsibility of the Land Deed Official (PPAT) in this process, and the inheritance system in Indonesia in accordance with Article 111 of the Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency Head No. 16 of 2021. The objectives are to analyze the legal consequences of transferring inheritance without heirs' consent, PPAT's responsibility regarding the deeds made, and the applicable inheritance system. The research aims to enhance knowledge on legal consequences and PPAT's responsibility and provide an understanding of Indonesia's inheritance system. The methodology is normative juridical with a descriptive approach, utilizing secondary legal materials through literature study and interviews. Conclusions indicate that the transfer of inheritance without all heirs' consent is invalid and can be annulled by the court, with PPAT holding significant responsibility to ensure the legality of the transfer process. Recommendations are provided for all parties to ensure compliance with legal procedures to protect heirs' rights and prevent legal disputes.